The Role of International Organizations in Handling Covid-19 Pandemic - Nabila, Alya; Larasati, Kandi Kirana (SASI, 2022)
Introduction: The spread of the Covid-19 virus after being designated as a pandemic by the WHO (World Health Organization) in early 2020 had a negative impact on the sustainability of life in the world. The hampering of activities due to lockdown policies to break the chain of transmission of the virus, paralyzed the movement of the world economy.Purposes of the Research: This study aims to find out the development of handling the Covid-19 virus as a pandemic and the role of WHO as an international health organization in equalizing vaccine availability.Methods of the Research: Normative juridical approach method with a statute approach, a historical approach and an analytical approach.Results of the Research: That as an effort to address inequality of access and distribution of Covid-19 vaccines between poor and rich countries, WHO formed a cooperation forum with the Global Alliance for Vaccines and Immunizations (GAVI), Vaccine Alliance, Coalition for Epidemic Preparedness Innovations (CEPI), and UNICEF namely Covid-19 Vaccines Global Access (COVAX) which has set up a pricing mechanism for rich countries to pay a requisite fees as a form of subsidize to poor countries.